Cost-effectiveness of tyrosine kinase inhibitor treatment strategies for chronic myeloid leukemia in South Africa - Woudberg, Rochelle; Sinanovic, Edina (Frontiers in Pharmacology, 2025)
BackgroundThe treatment of chronic myeloid leukemia through tyrosine kinase inhibitors (TKIs) has achieved promising efficacy and safety outcomes, however the costs are associated with a substantial economic burden. The objective of this study was to develop a Markov model with a 20-year time horizon to assess the cost effectiveness of TKIs from a public healthcare system perspective in South Africa.MethodsWe constructed a Markov model to compare three strategies in which treatment was initiated with either imatinib, nilotinib, or dasatinib. Treatment was switched to another TKI in the case of intolerance or resistance to the initial TKI. Effectiveness and utility data were obtained from published literature. Cost data was obtained from local sources for generic imatinib and branded second-generation TKIs and based on national tariffs. Outcomes were reported in total costs and quality-adjusted life years (QALYs). Outcomes were based on calculated incremental cost effectiveness ratios (ICERs) and compared to a willingness-to-pay (WTP) threshold. Sensitivity analyses were conducted to determine the robustness of the model outcomes.ResultsThe base-case results showed that imatinib was favored over nilotinib and dasatinib by having the lowest cost at $120 719.55 and providing 5.93 QALYs. Compared to imatinib strategy, nilotinib had an ICER of $26 620.27 per QALY and dasatinib had an ICER of $35 934.94 per QALY, both exceeding the WTP threshold of $18 760 per QALY gained. The sensitivity analysis indicated the robustness of the results.ConclusionImatinib remains the most cost-effective first-line treatment for adults diagnosed with CML in South Africa, with a high probability of being cost-effective across a range of WTP thresholds. Nilotinib and Dasatinib, though offering clinical benefits, their affordability remains a challenge within the current healthcare system and should remain reserved for second-line treatment.